Differences in Seed Weight, Amino Acid, Fatty Acid, Oil, and Squalene Content in γ-Irradiation-Developed and Commercial Amaranth Varieties (Amaranthus spp.) - Monika Szabóová; Michal Záhorský; Ján Gažo; Jeroen Geuens; Ann Vermoesen; Els D’Hondt; Andrea Hricová (Plants, 2020)
Grain amaranth is known as an alternative crop with exclusive nutritional value and health benefits. The purpose of this study was to investigate the effect of gamma irradiation on quantitative and qualitative amaranth seed traits, including 1000-seed weight, amino acids, fatty acids content, oil, and squalene yield. Two Slovak mutant varieties “Pribina” (A. cruentus) and “Zobor” (A.hypochondriacus x A. hybridus) were evaluated and compared to nonirradiated controls Ficha (A. cruentus L.) and K-433 (A. hypochondriacus x A. hybridus) and commercial varieties, Aztec (A. cruentus L.), Plainsman and Koniz (A. hypochondriacus x A. hybridus). Mutant varieties, “Pribina” and “Zobor”, showed superior 1000-seed weight performance compared to all investigated amaranth samples. The change in quantitative seed trait was accompanied by significantly higher oil and squalene content compared to commercial varieties. Moreover, significantly higher content of essential linoleic acid was detected in mutant variety “Zobor”. The present findings suggest that seeds of irradiation-derived varieties have high nutritional potential and can be used as a supplementary crop in the human diet.